2013
DOI: 10.1039/c3sm27912j
|View full text |Cite
|
Sign up to set email alerts
|

Imaging stress and strain in the fracture of drying colloidal films

Abstract: Drying-induced fracture limits the applications of thin films based on colloidal materials. To better understand the mechanics of drying, we directly measure the microscopic distribution of strain and stress of a colloidal silica film during the course of drying and cracking. We observe the build-up and release of internal stresses inside the film before and after the opening of individual cracks, and extract a critical stress for fracture of approximately 1 MPa. We also find an inherent time scale for stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(57 citation statements)
references
References 46 publications
2
55
0
Order By: Relevance
“…In these cases, the development of analytical and numerical methods for the growth dynamics of multiple cracks has been a decades-long challenge 10 . More recently, the study of fracture patterns in soft materials has become a topic of specific interest due to the novel applications of these materials 2,[11][12][13][14] . Particular attention has been paid to the formation and paths of cracks in gels and colloids.…”
Section: Introductionmentioning
confidence: 99%
“…In these cases, the development of analytical and numerical methods for the growth dynamics of multiple cracks has been a decades-long challenge 10 . More recently, the study of fracture patterns in soft materials has become a topic of specific interest due to the novel applications of these materials 2,[11][12][13][14] . Particular attention has been paid to the formation and paths of cracks in gels and colloids.…”
Section: Introductionmentioning
confidence: 99%
“…For example, during film processes, which are important for optoelectronics, magnetic and electronic materials [6][7][8][9], internal stresses often arise affecting the mechanical stability and strength of the film [9][10][11][12][13][14][15][16][17][18]. Here we study increasingly confined colloidal crystals to investigate how changes in their microstructure affect the microscopic stresses ultimately responsible for their bulk mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al have also measured the Young’s Modulus of films of the same type of silica particles that were used in this study and found it to be ~100 MPa19. These values predict d ~ 3.3 h, as opposed to the data in Fig.…”
Section: Resultsmentioning
confidence: 54%